PENINGKATAN KINERJA ALAT UJI KUAT TEKAN BEBAS DARI MANUAL KE MOTOR LISTRIK - Pahinggis, Mayda; Wakidi (Politeknik Negeri Jakarta, 2024)
The unconfined compression test apparatus is an essential tool in soil mechanics laboratories to evaluate the shear strength of soil. The apparatus at Jakarta State Polytechnic has been in use since 1982 with a manual drive system, which often results in inconsistent strain rates and inaccurate test results. This study aimed to enhance apparatus performance by replacing the manual drive with an electric motor drive system. The modification stages included design, fabrication, and performance testing. The results demonstrated that the modified apparatus maintained a stable strain rate between 0.52% and 1.95% per minute, fully complying with the required standard range of 0.5%–2% per minute. Compared to the manual system, the electric-driven apparatus improved test accuracy by 15%, reduced operator-related deviations by 20%, and increased repeatability by 25%. These findings indicate that the modification not only improved accuracy and efficiency but also ensured compliance with testing standards, making the apparatus more reliable for laboratory applications.